Ghana National Health Insurance Scheme : Improving Financial Sustainability Based on Expenditure Review - Wang, Huihui (Washington, DC: World Bank, 2017)
Ghana National Health Insurance Scheme (NHIS) was established in 2003 as a major vehicle to achieve the country’s commitment of Universal Health Coverage. The government has earmarked value-added tax to finance NHIS in addition to deduction from Social Security Trust (SSNIT) and premium payment. However, the scheme has been running under deficit since 2009 due to expansion of coverage, increase in service use, and surge in expenditure. Consequently, Ghana National Health Insurance Authority (NHIA) had to reduce investment fund, borrow loans and delay claims reimbursement to providers in order to fill the gap.